Pengaruh Konseling Saat Antenatal Care (ANC) Terhadap Pengetahuan Dan Sikap Ibu Hamil Tentang Tanda-Tanda Bahaya Kehamilan Di Wilayah Kerja Puskesmas Kapasa - Eppang, Yudiarsi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: The purpose of this study was to determine the effect of counseling during Antenatal care (ANC) on the knowledge and attitudes of pregnant women about the danger signs of pregnancy in the Kapasa health center coverage area.Â Methods: In this study, using a pre-experimental design design with the One Group Pre test and Post test approach and using purposive sampling research techniques. The number of samples is 16 people. The sampling technique uses the Federer formula. Data was collected by means of a questionnaire, data analysis used univariate and bivariate analysis using distribution tabels and Wilcoxon statistical test with 95% confidence degrees.Â Results: The results showed that the results of the Wilcoxon test for knowledge obtained p value = 0.011 which means that there is an effect of counseling on knowledge of pregnant women. And the Wilcoxon test results obtained p value = 0.025, which means there is an effect of counseling on the attitude of pregnant women.Â Conclusion: there is an effect of counseling during antenatal care on attitudes of pregnant women.